The Husband’s Expression of Love in the Shin Atashin’chi Anime - Oktaviani, Bilqis Rifkah; Febrianty, Fenny (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
In literary works, love is a popular theme. Love can be shown in many various ways. There are five different methods to show love, or the language of love: words of affirmation, physical touch, quality time, acts of service, and receiving gifts. In the anime Atashin'chi, the characters all show love in various ways. This study intends to examine how the husband character in the anime Atashin'chi displays love. The semiotic theory of John Fiske is combined with the descriptive analysis method in this study. The main study subject is the anime Atashin'chi by Shin-Ei Animation. The study showed how the husband character in the anime Atashin'chi employs the formal expression of acts of service by expressing and receiving affection through acts rather than words.of service.